Sleep duration and overactive bladder syndrome in US adults: a propensity score matching cohort study using NHANES 2005–2018 - Wang, Jia-Jia; Jin, Ai-Hong; Hu, Ling-Min; Tu, Xiu-Wei; Huang, Xiao-Peng; Mo, Li-Cai (Frontiers in Neurology, 2025)
ObjectiveThe association between sleep duration and overactive bladder (OAB) risk remains underexplored. The aim of this study was to assess this relationship in U.S. adults using National Health and Nutrition Examination Survey (NHANES) data.MethodsThis cross-sectional study included 24,360 participants aged 20–80 years with OAB who completed the NHANES (2005–2018). NHANES Kidney Conditions-Urology Questionnaire data and the Overactive Bladder Symptom Score (OABSS) were collected. Sleep duration was self-reported by the participants. Propensity score matching (PSM) and multivariate logistic regression were employed to control for confounding variables, whereas a generalized additive model (GAM) was utilized to explore the nonlinear relationship between sleep duration and OAB.ResultsShort sleep (<6 h) significantly increased OAB risk (OR 1.37; 95% CI, 1.21–1.55; p < 0.01). A U-shaped relationship between sleep duration and OAB was observed, suggesting that approximately 6 h of sleep is optimal for minimizing OAB risk. Additional risk factors for OAB included female sex, older age, higher BMI, lower education and income levels, hypertension, diabetes, and smoking.ConclusionBoth insufficient and excessive sleep durations were independently linked to increased OAB risk, and the optimal sleep duration to minimize OAB risk was approximately 6 h. These findings emphasize the importance of targeted prevention and intervention strategies focused on sleep and other modifiable risk factors for OAB. Further research is needed to better understand the biological mechanisms linking sleep duration and OAB.